Business literacy and development: Evidence from a randomized controlled trial in rural Mexico - Gabriela Calderon; Jesse M. Cunha; Giacomo De Giorgi (Banco de México, 2013)
This paper explores whether the poor performance of many micro-enterprises can be explained by a lack of basic business skills. We randomized the offer of a free, 48-hour business skills course to female entrepreneurs in rural Mexico. We find that those assigned to treatment earn higher profits, have larger revenues, serve a greater number of clients, are more likely to use formal accounting techniques, and more likely to be registered with the government. Economically significant indirect treatment effects on those entrepreneurs randomized out of the program, yet living in treatment villages are observed. We present a simple model that helps interpret our results, and consistent with the theoretical predictions, we find that entrepreneurs with lower baseline profits are the most likely to quit their business post-treatment, and that the positive impacts of the treatment are increasing in entrepreneurial quality.
Keywords: C93; I25; O12; O14; 330; business literacy; economic development; micro-enterprise; Kleinstunternehmen; Unternehmenserfolg; Gründungsausbildung; Weibliche Führungskräfte; Ländliche Wirtschaft; Mexiko